Artificial Intelligence for Human Learning & Behaviour Change - Sadarangani Divya; Arju.K. Desai; Vivek Dave (Utan Kayu Publishins, 2025)
This paper explores the potential of artificial intelligence (AI) in facilitating human learning and promoting behaviour change. By employing machine learning algorithms, natural language processing, and data analysis, AI systems can provide personalized learning experiences, identify learning gaps, and adapt to individual learning styles. Furthermore, AI can be utilized to create nudges and interventions that encourage positive behaviour change, offering promising applications in fields such as health, finance, and environmental conservation. The paper also discusses ethical considerations and challenges, emphasizing the importance of transparency, fairness, and privacy in AI-driven learning and behaviour change systems